LITHOSPHERIC MANTLE COMPOSITION AND STRUCTURE VARIATIONS UNDER THE SIBERIAN PLATFORM KIMBERLITE FIELDS OF DIFFERENT AGES - N. P. Pokhilenko; V. P. Afanasiev; A. M. Agashev; L. N. Pokhilenko; N. S. Tychkov (Геодинамика и тектонофизика)
We discuss herein the differences both in composition and structure of the lithospheric mantle of the Siberian Platform under kimberlite fields of different ages. Having analyzed the pyrope garnets from kimberlites of different ages this study aimed to identify the genesis, extent and probable causes for the evolution of the composition and structure of the lithospheric mantle within various SP blocks. Acquired results revealed noticeable differences in the lithosphere thickness of different blocks for Middle Paleozoic and Mesozoic, as well as within the same time. It was found, that the greatest differences in the thickness of the lithosphere individual blocks are typical for the Middle Paleozoic. The results obtained for pyrope garnets from the Paleozoic sedimentary secondary collectors was used to get direct evidence on the existence of thick lithosphere blocks (230–240 km) under the southern margin of the Olenek uplift, north and south of the Kyutyungde trough, as well as under the western and eastern margins of the Udzhinsky uplift. Significant variations in the intensity and extent of silicate-type metasomatism were identified by investigating of pyropes from peridotites of the lithospheric mantle, sampled by kimberlites of both Middle Paleozoic and Triassic fields. Direct evidence indicates high prospects for discovering new fields of diamondiferous high-grade kimberlites of the Middle Paleozoic age in some areas of the Siberian Platform, primarily in its Arctic region.